Evaluation of Self-Control and Resilience as Psychological Predictors of Regular Physical Exercise in the Elderly - Caturia Sasti Sulistyana; Wiwin Sulistyawati; Satria Eureka Nurseskasatmata; Siska Christianingsih; Abdul Fauzi (Adi Husada Nursing Journal, 2025)
Regular physical exercise is crucial for healthy aging, yet many elderly face psychological barriers that prevent consistent participation. This study analyzed self-control and resilience as psychological predictors of regular physical exercise in the elderly, used a quantitative correlational design. Sixty respondents aged 60-70 years with simple random sampling. Data were collected used Brief Self-Control Scale and CD-RISC-10 for resilience instruments, while the level of participation in regular physical exercise was measured based on attendance to the physical exercise four times a week. The data were then analyzed using Pearson correlation and multiple linear regression. The results showed a significant correlation between self-control (r=0.721, p-value 0.002), resilience (r=0.618, p-value 0.003). Regression analysis revelead that self-control (Î² = 0.55, p-value 0.000) and resilience (Î² = 0.51, p-value 0.002) significantly predicted exercise behavior, explaining 28% of the variance (RÂ² = 0.28). These findings suggest that elderly with higher self-control and resilience are more likely to maintain a regular exercise. The results support the development of health promotion programs that incorporate psychological training to strengthen self-regulation and adaptability in the elderly. Future research should explore the other predictors of physical exercise in elderly. Strengthening psychological resources is a key strategy to well-being in elderly.